The Position and Application of Islamic Legal Maxims (Qawaaid Al-Fiqhiyyah) in the Law of Evidence (Turuq Al-Hukmiyyah) - Mohamad Ismail Bin Mohamad Yunus (Universitas Lampung, 2019)
The Position and Application of Islamic Legal Maxims (Qawaaid Al-Fiqhiyyah) in the Law of Evidence (Turuq Al-Hukmiyyah)Islamic legal maxims had always held and will continue to hold a special position in jurisprudence. Jurists of all schools generally accept legal maxims as a basis of coming up with Shariah opinions. This is especially true if these maxims are based on the Holy Quran and the Prophetic traditions. Legal maxims can be used as evidence in extracting rules if it is based on the Holy Quran and the Sunnah because its use is an extension of the original proof, and thus, this article will relate some of the important legal maxims relating to the law of evidence.